2007
DOI: 10.1111/j.1439-037x.2007.00251.x
|View full text |Cite
|
Sign up to set email alerts
|

Glycinebetaine Accumulation, Physiological Characterizations and Growth Efficiency in Salt‐tolerant and Salt‐sensitive Lines of Indica Rice (Oryza sativaL. ssp.indica) in Response to Salt Stress

Abstract: The aim of this research was to investigate betaine aldehyde dehydrogenase (BADH) and glycinebetaine (Glybet) biosynthesis in photoautotrophic rice seedlings. The role of Glybet on physiological and growth responses to salt stress in both salt-tolerant and salt-sensitive lines is to be investigated. The BADH activity in salt-tolerant seedlings cultured under extreme salt stress (342 mm NaCl) progressively increased during the first few hours until it peaked after 72 h. This was about 2.5 times greater than in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(48 citation statements)
references
References 57 publications
4
44
0
Order By: Relevance
“…), stomatal conductance (g s ; mmol m −2 s −1 ), transpiration rate (E; mmol m −2 s −1 ) and water use efficiency (WUE; %) were measured using a Portable Photosynthesis System (Model LI 6400, LI-COR®Inc, Lincoln, Nebraska, USA) with an Infrared Gas Analyser following Cha-um et al (2007). WUE was calculated according to the equation: WUE ¼ P n =E ½ Â100.…”
Section: Physiological Charactersmentioning
confidence: 99%
“…), stomatal conductance (g s ; mmol m −2 s −1 ), transpiration rate (E; mmol m −2 s −1 ) and water use efficiency (WUE; %) were measured using a Portable Photosynthesis System (Model LI 6400, LI-COR®Inc, Lincoln, Nebraska, USA) with an Infrared Gas Analyser following Cha-um et al (2007). WUE was calculated according to the equation: WUE ¼ P n =E ½ Â100.…”
Section: Physiological Charactersmentioning
confidence: 99%
“…4). Loss of chlorophyll pigment (Bahaji et al 2002;Siringam et al 2009) and reductions in the F v /F m ratio under salinity stress were also reported for other rice cultivars (Abdullah et al 2001;Cha-um et al 2007;Djanaguiraman et al 2006;Siringam et al 2009;Yamane et al 2008) as well as in sorghum (Netondo et al 2004), naked oat (Zhao et al 2007), wheat (Zheng et al 2009) and chickpea (Eyidogan and Ö z 2007).…”
Section: Discussionmentioning
confidence: 79%
“…Net photosynthetic rate (P n ; µmol m -2 s -1 ), transpiration rate (E; mmol m -2 s -1 ), stomatal conductance (g s ; mmol H 2 O m -2 s -1 ) and water use efficiency (WUE; %) were measured using a Portable Photosynthesis System (Model LI 6400, LI-COR  Inc, Lincoln, Nebraska, USA) with an Infra-red Gas Analyser following Cha-um et al (2007). WUE was calculated according to equation: WUE (%) = [P n /E] × 100.…”
Section: Methodsmentioning
confidence: 99%